The clickable corporation : successful strategies for capturing the internet advantage - Rosenoer, Jonathan; Armstrong, Douglas; Gates, J. Russell (New York : Free Press, 1999)
Describes Internet opportunities and looks at twenty-five companies already established on the Internet.
Foreword / Thomas B. Kelly -- The Future is Only a Click Away -- Click with Information -- Click with Choice -- Click with Convenience -- Click with Customization -- Click with Savings -- Click with Community -- Click with Entertainment -- Click with Trust.
"An Arthur Andersen best-practices book."
Includes index.
Keywords: Business enterprises -- Computer networks; Internet; E-commerce.